A Nexus between Working Capital Management and Profitability: A Case Study of Pharmaceutical Sector in Pakistan - Zeeshan Ahmed; Muhammad Zahid Awan; Muhammad Zulqarnain Safdar; Tafakhar Hasnain; Muhammad Kamran (International Journal of Economics and Financial Issues, 2016)
Amongst all the issues of financial management, the issue of routine capital management is critical one. The reason is; it always elucidates a direction to help out a firm to acquire energy in short run. In broader sense, working capital is the sum of those items exposed on firm's balance sheet as short term assets i.e. cash, marketable securities, account receivables and inventories. The central point of this research study is to critically discuss the impact of working capital management on financial outcomes of Pharmaceutical Sector in Pakistan. To attain this land mark researcher also observed the affiliation between independent variables utilized to gauge working capital and profitability measured by return on investment and return on equity of the firm. The present study used secondary data for the analysis. The data utilized in this study is extracted from the annual reports of Pharmaceutical companies quoted in Karachi Stock Exchange (KSE). The current research used different statistical tests to examine the impact of working capital management on profitability. According to the results of regression analysis, the null hypothesis of the study is rejected because all the variables related to working capital negatively affect the profitability of Pharmaceutical firms measured in terms of ROI and ROE. Results of correlation analysis indicate that there is negative relationship between working capital and profitability which is significant at 1% level. Findings of present work suggest that mangers can increase the profitability of the firm by keeping the cash conversion cycle to an optimum level.